INVESTIGATING STUDENTS’ ATTITUDES TOWARDS THE EFFECT OF IMPLEMENTING THE READER- RESPONSE APPROACH IN LITERATURE CLASSES ON DEVELOPING THEIR CRITICAL THINKING - HASSAN, HAZHA SALIH; BAJALANI, FATIMAH R. HASAN AL; ISMAIL, KHADEEJA SAEED (Journal of Duhok University, 2023)
The current article aims at investigating EFL university students’ attitudes towards the effect of implementing the reader-response approach (Rosenblatt’s Transactional Theory) on developing their critical thinking. To this end, the study adopted quantitative method of data collection. A questionnaire was administrated to 30 EFL undergraduate sophomore students at Salahaddin University-Erbil / College of Basic-Education. The results revealed that students had positive attitudes towards the use of the approach. The selected sample of students also considered the critical questioning activity more powerful than the rest of the activities in improving their critical thinking